Atopic dermatitis: a restropective study of associated factors in a dermopathic canine population - do Amarante, Cristina Fernandes; Ramadinha, Regina Ruckert; Pereira, Maria Júlia Salim (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Amarante C.F., Ramadinha R.R. & Pereira M.J.S. Atopic dermatitis: a restropective study of associated factors in a dermopathic canine population. [Dermatite atópica: um estudo retrospectivo dos fatores associados em uma população canina dermopata.] Revista Brasileira de Medicina Veteriná- ria, 37(Supl.1):13-17, 2015. Curso de Pós-Graduação em Ciências Veterinárias, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 7, Seropédica, RJ 23897-970, Brasil. E-mail: cristinaf.amarante@gmail.com Canine atopic dermatitis (AD) is a pruriginous inflammatory disease related to the production of IgE antibodies and frequently, diagnosed in the clinical veterinary practice. However, there are many controversies about the predisposing factors. The objective of this study was to analyze the contribution of the sex, age, breed, castration, time of year, the use of perfume and cleaning products as predisposing factors for the occurrence of AD using binomial generalized linear regression model estimating the prevalence ratio as a measure of effect. The clinical records of 2,280 dogs attended by the Section of Dermatology Small Animal Hospital of the Rural Federal University of Rio de Janeiro, between 2005 and 2010, were reviewed and 1,462 dogs were included in the study. Bivariate and multivariate analyses were performed using a generalized binomial linear regression model. Significance was set at a p-value of ≤ 0.05. Atopic dermatitis was diagnosed in 36.1% (528/1462) of the canine population studied and was associated with females [PR= 1.204 (1.048 to 1.384)], adults [PR= 2.045 (1.542 to 2.711)], the dry season [PR= 0.840 (0.734 to 0.962)], the use of perfumes [PR= 1.271 (1.089 to 1.483)]. Thus, atopic dermatitis prevalence in the study population was higher in females, adults, in which applied perfumes and in the rainy season. . This study constitutes a new approach to the epidemiological aspects of canine atopic dermatitis in Brazil, but requires a better understanding of the relationships between the explanatory variables and outcome through longitudinal studies.